A high-elastic silk fibroin hydrogel and its photocuring preparation method and application
The photocuring system of riboflavin and hydrogen peroxide cross-links silk fibroin macromolecules under ultraviolet light, solving the problem of insufficient light transmittance and mechanical properties of existing silk fibroin hydrogels, and high light transmittance and High mechanical resilience silk fibroprotein hydrogel is suitable for biomedical materials and 3D printed substrates, achieving biocompatibility and process simplification.
Patent Information
- Application Number
- CN202211567124.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-07
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-12-07
AI Technical Summary
The existing silk fibroprotein hydrogels have shortcomings in light transmittance and mechanical properties, and the chemical reagents added to the traditional preparation methods affect biocompatibility.
The photocuring system of riboflavin and hydrogen peroxide is adopted to cross-link silk fibroprotein macromolecules under ultraviolet light irradiation, shorten the gel formation time, and improve light transmittance and mechanical resilience.
Prepare silk fibroprotein hydrogel with good light transmittance, high mechanical resilience and excellent biocompatibility, without organic reagent residues. It is suitable for biomedical materials and 3D printed substrates. The process flow is short and easy to produce on a large scale. .
Smart Images

Figure CN116041735B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer gels, and in particular relates to a highly elastic silk fibroin hydrogel and a photocuring preparation method and application thereof. Background Art
[0002] Hydrogels refer to materials that can absorb large amounts of water without dissolving. They are formed by chemical or physical crosslinking of hydrophilic natural or synthetic polymers. Due to their high water absorption and water retention properties, hydrogels have a wide range of applications: such as facial masks, fever-reducing patches, preservatives in the food industry, and drug carriers in the medical field. At present, there are many methods for preparing hydrogels reported at home and abroad, such as chemical crosslinking, physical crosslinking, and biocatalysis. Different preparation methods can prepare hydrogels with different properties, thereby meeting the application needs of different fields.
[0003] Silk fibroin is a natural protein extracted from silk. It has excellent mechanical properties, processability, biocompatibility and biodegradability. It has received extensive attention in the fields of tissue engineering and drug sustained release, and has been used to develop products in the form of fibers, films, scaffolds, microspheres, etc. For example, CN114409926A provides a method for preparing a self-healing antifreeze conductive silk fibroin hydrogel, which improves the three major shortcomings of ordinary silk fibroin hydrogels, namely, no antifreeze, no self-healing, and uneven distribution of conductive materials, so that it has broad application prospects in the field of flexible electronic products; CN109824922A provides a silk fibroin hydrogel with infrared light response, and the obtained silk fibroin hydrogel has a high photothermal conversion efficiency; CN109431971A provides a method for preparing an injectable drug-loaded hydrogel, which can be used for local injection, including but not limited to intratumoral injection, tumor-adjacent injection and other solid tumor treatments.
[0004] The above patents prepare hydrogels based on regenerated silk fibroin. Most of the preparation methods used use chemical methods to form a large number of crystallized areas inside the silk fibroin. Although the structure is stable, the obtained hydrogel has problems such as poor light transmittance and unsatisfactory mechanical properties. In order to make the silk fibroin hydrogel have good light transmittance, CN109180964A uses monomer N-vinyl pyrrolidone dissolved in a silk fibroin solution, and the polyvinyl pyrrole macromolecule formed by the polymerization of N-vinyl pyrrolidone by ultraviolet light and horseradish peroxidase is physically entangled with the silk fibroin molecular chain, thereby obtaining a new type of silk fibroin hydrogel with good light transmittance and excellent degradation performance. However, since this method adds more chemical reagents inside the gel, it will have a greater impact on the biocompatibility of the material.
[0005] In view of this, the present invention prepares a silk fibroin hydrogel based on a silk fibroin photocuring system. The silk fibroin hydrogel has safe components, no biological toxicity, good mechanical resilience, no organic reagents added during the preparation process, and a fast gelation speed. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a highly elastic silk fibroin hydrogel and a photocuring preparation method and application thereof in view of the above-mentioned deficiencies in the prior art. The silk fibroin hydrogel has good light transmittance, excellent biocompatibility, and high elasticity, and is particularly suitable for the field of biomedical materials. The photocuring preparation process is time-saving and highly efficient.
[0007] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0008] Provided is a high-elastic silk fibroin hydrogel, which is obtained by adding riboflavin and hydrogen peroxide to a silk fibroin solution and performing photocuring under ultraviolet light irradiation.
[0009] The present invention also includes a method for preparing the above-mentioned highly elastic silk fibroin hydrogel, and the specific steps are as follows:
[0010] S1. preparing a silk fibroin solution: placing raw silk in a sodium carbonate aqueous solution and heating and soaking it for degumming to obtain degummed silk fibroin fibers, immersing the obtained degummed silk fibroin fibers in a LiBr aqueous solution and heating and dissolving them to obtain a crude solution, placing the obtained crude solution in a dialysis bag, and dialyzing it in deionized water at low temperature, filtering the dialyzed solution to remove impurities, and diluting it to obtain a silk fibroin solution;
[0011] S2, mixing the silk fibroin solution obtained in step S1 and the riboflavin aqueous solution uniformly to obtain a mixed solution, and then adding the hydrogen peroxide solution to the mixed solution, and mixing them thoroughly to obtain a pre-reaction solution;
[0012] S3, placing the pre-reaction solution obtained in step S2 under ultraviolet light for photocuring to obtain a highly elastic silk fibroin hydrogel.
[0013] According to the above scheme, the concentration of the sodium carbonate aqueous solution in S1 is 0.1-0.5wt%, the mass volume ratio of the raw silk to the sodium carbonate aqueous solution is 1g / 10-100mL, the degumming treatment temperature is 45-100°C, and the degumming treatment time is 1-8h.
[0014] According to the above scheme, the concentration of the LiBr aqueous solution in S1 is 1-10 mol / L, the mass volume ratio of the degummed silk fibroin fiber to the LiBr aqueous solution is 1 g / 1-20 mL, the degummed silk fibroin fiber is immersed in the LiBr aqueous solution and heated to dissolve at a temperature of 45-85° C., and the heating and dissolving time is 0.5-3 h.
[0015] According to the above scheme, the S1 low-temperature dialysis temperature is 0-4°C and the low-temperature dialysis time is 1-5 days.
[0016] According to the above scheme, the concentration of the silk fibroin solution in S1 is 1.5-7wt%.
[0017] According to the above scheme, the concentration of the riboflavin aqueous solution in S2 is 0.05-10 mM (mmol / L), and the volume ratio of the silk fibroin solution to the riboflavin aqueous solution is 5-20:1.
[0018] According to the above scheme, the volume percentage concentration of the hydrogen peroxide solution in S2 is 5-30%, and the volume ratio of the hydrogen peroxide solution to the mixed solution is 1:5-30.
[0019] According to the above scheme, the power of S3 UV lamp is 100-900W, and the photocuring reaction time is 2-30min.
[0020] The present invention also includes the application of the above-mentioned highly elastic silk fibroin hydrogel in the field of biomedical materials. For example, by utilizing the characteristics of the hydrogel with good elasticity, high porosity and short preparation time, cells are uniformly dispersed in the silk fibroin hydrogel for culture to prepare a silk fibroin biomedical scaffold.
[0021] And the application of the above-mentioned highly elastic silk fibroin hydrogel in the field of 3D printing substrate.
[0022] The present invention adopts a photocuring method to prepare the silk fibroin hydrogel, and cross-links are formed by mutual entanglement between silk fibroin macromolecules. The internal crystalline structure is relatively low, mainly a silk I structure, so that the hydrogel not only has good light transmittance, but also has extremely high elasticity and excellent biocompatibility.
[0023] The present invention is based on regenerated silk fibroin, riboflavin and hydrogen peroxide as a photocuring system, and the silk fibroin hydrogel is cured under ultraviolet light. Riboflavin can be excited to produce a triplet state under ultraviolet light, react with oxygen to form oxygen free radicals, and oxygen free radicals can promote the mutual entanglement between silk fibroin macromolecules to form a gel. However, the rate of photocrosslinking silk fibroin gel with riboflavin alone is extremely slow. Therefore, this study proposes riboflavin and hydrogen peroxide as a new photocuring system, wherein hydrogen peroxide decomposes under ultraviolet light to produce oxygen, which can be used as an oxygen source to provide more oxygen for the system, promote the reaction, and greatly shorten the time of gel formation. The hydrogel prepared by the present invention not only has extremely high mechanical resilience, but also has excellent light transmittance. Due to the shortening of the gel time, the mixed solution can be mixed with cells and then photocured, and the cells can be evenly coated inside the gel as a carrier of cells, expanding the application of silk fibroin-based hydrogel in the biomedical field.
[0024] In addition, under the photocuring system of the present invention, the gel formation process is mainly the entanglement between silk fibroin macromolecules, and there are very few β-folded structures inside the silk fibroin (the silk fibroin hydrogel prepared by the traditional method has a large number of β-folded structures inside. Although the hydrogel with β-folded structure has high strength, it has low elasticity, making the hydrogel brittle and easily crushed under pressure). Therefore, the hydrogel prepared by the present invention has good mechanical resilience.
[0025] The beneficial effects of the present invention are: 1. The silk fibroin hydrogel provided by the present invention has no organic reagent residue, no biological toxicity, excellent mechanical resilience, good light transmittance, and has good market application prospects in the fields of biomedical materials, 3D printing substrates, etc.; 2. The preparation method provided by the present invention greatly shortens the time for gel formation, is simple to operate, has a short process flow, and is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 These are photos of the pre-reaction solution before and after photocuring in Example 1 of the present invention;
[0027] Figure 2 is the XRD pattern of the silk fibroin hydrogel prepared in Example 1;
[0028] Figure 3 This is a graph showing the resilience test of the silk fibroin hydrogel prepared in Example 1;
[0029] Figure 4 This is a comparison diagram of the silk fibroin hydrogel prepared in Example 1 before and after the compression mechanical test;
[0030] Figure 5 This is a test diagram of the compression strength of the silk fibroin hydrogel and pure silk fibroin hydrogel prepared in Example 1;
[0031] Figure 6 This is a biocompatibility test diagram of the silk fibroin hydrogel prepared in Example 1;
[0032] Figure 7 This is an electron microscope test image of the silk fibroin hydrogel prepared in Example 1-3 after vacuum freeze-drying;
[0033] Figure 8 This is a comparison chart of the water holding capacity of the silk fibroin hydrogels prepared in Examples 1-3;
[0034] Fig. 9 This is a comparison chart of the transmittance of 6 types of silk fibroin hydrogels prepared in Example 4. DETAILED DESCRIPTION
[0035] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.
[0036] Example 1
[0037] A highly elastic silk fibroin hydrogel, the preparation method of which comprises the following specific steps:
[0038] S1. Prepare silk fibroin solution: place 30 g of raw silk in 900 mL of 0.1 wt% sodium carbonate aqueous solution, boil and soak for 1.5 h to perform degumming treatment to obtain degummed silk fibroin fibers, immerse the obtained degummed silk fibroin fibers in 300 mL of 10 mol / L LiBr aqueous solution, heat to 80° C. and dissolve for 3 h to obtain a crude solution, place the obtained crude solution in a dialysis bag, dialyze in 0° C. deionized water for 5 days, filter the dialyzed solution to remove impurities, and dilute to a concentration of 1.5 wt% to obtain a silk fibroin solution for standby use;
[0039] S2, mixing the silk fibroin solution obtained in step S1 with a 0.5 mM riboflavin aqueous solution at a volume ratio of 20:1 to obtain a mixed solution, adding a 30 vol% hydrogen peroxide solution to the mixed solution at a volume ratio of 1:30, and mixing thoroughly to obtain a pre-reaction solution;
[0040] S3. The pre-reaction solution obtained in step S2 is placed under a 400 W ultraviolet lamp for 30 minutes to perform a photocuring reaction to obtain a highly elastic silk fibroin hydrogel.
[0041] Figure 1 These are photos of the pre-reaction liquid of this example before and after photocuring. The left side is the photo before UV light irradiation, and the right side is the photo after UV light irradiation. Using the tilting method for observation, it can be seen that when the bottle is tilted in the right picture, the liquid level does not change, indicating that a gel has been formed.
[0042] The silk fibroin hydrogel prepared in this example was further characterized by XRD. Figure 2 As shown, it can be seen that the prepared silk fibroin hydrogel has a diffraction peak at 19.7°, which mainly shows a silk I structure, indicating that the silk fibroin mainly reacts in the non-crystalline region during the formation of the hydrogel.
[0043] The resilience of the silk fibroin hydrogel prepared in this example was tested. The hydrogel was prepared into a cylinder with a diameter of 2 mm and a height of 5 mm, and a compression mechanical test was performed on a TMS-PRO texture analyzer. The test mainly performed three compressions, the first compression deformation was 20%, the second compression deformation was 40%, and the third compression deformation was 60%. The stress-strain curve of the silk fibroin hydrogel during compression and rebound is shown in FIG. Figure 3As shown, it can be seen that the area enclosed by the closed curve formed by the loading curve and the unloading curve is very small, that is, the elastic loss during the cyclic compression process is very small, indicating that the light-cured silk fibroin hydrogel prepared by the present invention has high elastic properties. Figure 4 The silk fibroin hydrogel prepared in this example is subjected to the above compression mechanical test before and after (actual object comparison diagram, from which it can be seen that the hydrogel has almost no change before and after compression, indicating that the hydrogel has good compression rebound performance.
[0044] The silk fibroin hydrogel prepared in this example was further subjected to a compressive strength test. The hydrogel was prepared into a cylinder with a diameter of 2 mm and a height of 5 mm, and a compression mechanical test was performed on a TMS-PRO texture analyzer. The deformation was set to 90%, and pure silk fibroin hydrogel was used as a control sample. The pure silk fibroin hydrogel was obtained by ultrasonic treatment of a 5 wt % silk fibroin solution at 300 W power for 1 min. Figure 5 It can be seen that the pure silk hydrogel ruptured when the compression deformation reached 40%, and its compression strength was about 20 kPa. The light-cured silk protein hydrogel in this embodiment began to rupture when the deformation reached 82%, and its compression strength reached about 80 kPa.
[0045] To further test the biocompatibility of the silk fibroin hydrogel prepared in this example, the endothelial cells were first resuspended with the culture medium, filtered, and the waste liquid was discarded to obtain the endothelial cells. The endothelial cells were then mixed with the pre-reaction solution of this example and then photocured under the conditions of this example to form a gel, so that the cells were encapsulated in the gel, and then placed in a 37° C. incubator for 7 days. Figure 6 This is a tracer staining photo of cells after 7 days of culture. Figure 6 It can be seen that there are a large number of cells inside the hydrogel after 7 days of cultivation, and the cells can proliferate well inside the hydrogel, indicating that the hydrogel has good biocompatibility.
[0046] Example 2
[0047] A highly elastic silk fibroin hydrogel, the preparation method of which comprises the following specific steps:
[0048] S1. Prepare silk fibroin solution: place 30 g of raw silk in 900 mL of 0.1 wt% sodium carbonate aqueous solution, boil and soak for 1.5 h to perform degumming treatment to obtain degummed silk fibroin fibers, immerse the obtained degummed silk fibroin fibers in 300 mL of 10 mol / L LiBr aqueous solution, heat to 80° C. and dissolve for 3 h to obtain a crude solution, place the obtained crude solution in a dialysis bag, dialyze in 0° C. deionized water for 5 days, filter the dialyzed solution to remove impurities, and dilute to a concentration of 2.5 wt% to obtain a silk fibroin solution for standby use;
[0049] S2, mixing the silk fibroin solution obtained in step S1 with a 0.5 mM riboflavin aqueous solution at a volume ratio of 20:1 to obtain a mixed solution, adding a 30 vol% hydrogen peroxide solution to the mixed solution at a volume ratio of 1:30, and mixing thoroughly to obtain a pre-reaction solution;
[0050] S3. The pre-reaction solution obtained in step S2 is placed under a 400 W ultraviolet lamp for 15 minutes to perform a photocuring reaction to obtain a highly elastic silk fibroin hydrogel.
[0051] Example 3
[0052] A highly elastic silk fibroin hydrogel, the preparation method of which comprises the following specific steps:
[0053] S1. Prepare silk fibroin solution: place 30 g of raw silk in 900 mL of 0.1 wt% sodium carbonate aqueous solution, boil and soak for 1.5 h to perform degumming treatment to obtain degummed silk fibroin fibers, immerse the obtained degummed silk fibroin fibers in 300 mL of 10 mol / L LiBr aqueous solution, heat to 80° C. and dissolve for 3 h to obtain a crude solution, place the obtained crude solution in a dialysis bag, dialyze in 0° C. deionized water for 5 days, filter the dialyzed solution to remove impurities, and dilute to a concentration of 5 wt% to obtain a silk fibroin solution for standby use;
[0054] S2, mixing the silk fibroin solution obtained in step S1 with a 0.5 mM riboflavin aqueous solution at a volume ratio of 20:1 to obtain a mixed solution, adding a 30 vol% hydrogen peroxide solution to the mixed solution at a volume ratio of 1:30, and mixing thoroughly to obtain a pre-reaction solution;
[0055] S3. The pre-reaction solution obtained in step S2 is placed under a 400 W ultraviolet lamp for 2 minutes to perform a photocuring reaction to obtain a highly elastic silk fibroin hydrogel.
[0056] The morphology of the silk fibroin hydrogel prepared in Examples 1-3 was characterized by electron microscopy after vacuum freeze-drying. Figure 7 As shown, Figure 7 a and d represent electron microscopic morphology images of the hydrogel with a silk fibroin concentration of 1.5% obtained in Example 1, b and e represent electron microscopic morphology images of the hydrogel with a silk fibroin concentration of 2.5% obtained in Example 2, and c and f represent electron microscopic morphology images of the hydrogel with a silk fibroin concentration of 5% obtained in Example 3. It can be seen that the hydrogel with a silk fibroin concentration of 1.5% has a pore diameter of 100-300um after freeze-drying, the hydrogel with a silk fibroin concentration of 2.5% has a pore diameter of 80-200um after freeze-drying, and the hydrogel with a silk fibroin concentration of 5% has a pore diameter of 50-100um after freeze-drying. Figure 7It can be seen that as the concentration of silk fibroin increases, the pores of the prepared hydrogel decrease and the pore size becomes smaller and smaller. This is because the increase in silk fibroin concentration causes more entanglement between silk fibroin molecules, increases the cross-linking degree of the hydrogel, and reduces the water storage space inside the gel, which is manifested as a decrease in pores and pore size. Therefore, hydrogels with different pore sizes can be prepared by adjusting the concentration of silk fibroin, and the morphology and structure of the prepared silk fibroin hydrogel can be regulated to meet different application requirements.
[0057] The water holding capacity of the silk fibroin hydrogels prepared in Examples 1-3 was further tested, and the results were as follows: Figure 8 As shown in the figure, when the silk fibroin concentration is 5%, the water holding rate of the hydrogel is about 1000%, when the silk fibroin concentration is 2.5%, the water holding rate of the hydrogel increases to about 2000%, and when the silk fibroin concentration is reduced to 1.5%, the water holding rate of the hydrogel increases to about 3000%. Figure 8 It can be seen that different silk fibroin concentrations will affect the water holding capacity of the hydrogel. The higher the silk fibroin concentration, the lower the water holding capacity of the produced hydrogel. This is because with the increase in silk fibroin concentration, the cross-linking formed by intermolecular entanglement increases, making the pores inside the hydrogel tighter, reducing the water storage space, and reducing the water holding capacity.
[0058] Example 4
[0059] A highly elastic silk fibroin hydrogel, the preparation method of which comprises the following specific steps:
[0060] S1. Prepare silk fibroin solution: place 30 g of raw silk in 900 mL of 0.1 wt% sodium carbonate aqueous solution, boil and soak for 1.5 h to degumming, obtain degummed silk fibroin fiber, immerse the obtained degummed silk fibroin fiber in 300 mL of 10 mol / L LiBr aqueous solution, heat to 80°C and dissolve for 3 h to obtain a crude solution, place the obtained crude solution in a dialysis bag, dialyze in 0°C deionized water for 5 days, filter the dialyzed solution to remove impurities, dilute to 1.5 wt%, 2.5 wt%, 5 wt% to obtain silk fibroin solution, and set aside;
[0061] S2, mixing the three silk fibroin solutions obtained in step S1 with 0.05 mM and 0.5 mM riboflavin aqueous solutions at a volume ratio of 20:1 to obtain six mixed solutions, adding 30 vol% hydrogen peroxide solution to the six mixed solutions at a volume ratio of 1:30, and mixing them thoroughly to obtain six pre-reaction solutions;
[0062] S3. The six pre-reaction solutions obtained in step S2 were all placed under a 400 W ultraviolet lamp for 20 minutes to perform a photocuring reaction to obtain six highly elastic silk fibroin hydrogels.
[0063] The light transmittance of the six silk fibroin hydrogels prepared in this example was tested, and the results were as follows: Fig. 9 As shown. Since riboflavin in this reaction system is a yellow solution, the main factor affecting the transmittance of this system is the concentration of riboflavin. Fig. 9 It can be seen that the higher the riboflavin concentration, the yellower the color of the hydrogel and the worse the light transmittance of the hydrogel. When the riboflavin concentration is 0.05mM, the light transmittance of the hydrogel is about 85%. When the riboflavin concentration increases to 0.5mM, the light transmittance of the hydrogel drops to about 75%. The riboflavin concentration can be adjusted according to different applications to achieve the desired balance between light curing rate and light transmittance.
[0064] Comparative Example 1
[0065] A silk fibroin hydrogel, in which only riboflavin is added without adding hydrogen peroxide during the preparation process, the specific steps are as follows:
[0066] S1. Prepare silk fibroin solution: place 30 g of raw silk in 900 mL of 0.1 wt% sodium carbonate aqueous solution, boil and soak for 1.5 h to perform degumming treatment to obtain degummed silk fibroin fibers, immerse the obtained degummed silk fibroin fibers in 300 mL of 10 mol / L LiBr aqueous solution, heat to 80° C. and dissolve for 3 h to obtain a crude solution, place the obtained crude solution in a dialysis bag, dialyze in 0° C. deionized water for 5 days, filter the dialyzed solution to remove impurities, and dilute to a concentration of 5 wt% to obtain a silk fibroin solution for standby use;
[0067] S2, fully mixing the silk fibroin solution obtained in step S1 with a 50 mM riboflavin aqueous solution at a volume ratio of 20:1 to obtain a pre-reaction solution;
[0068] S3. The pre-reaction solution obtained in step S2 is placed under a 400 W ultraviolet lamp for 3 hours to perform a photocuring reaction to obtain a silk fibroin hydrogel.
[0069] In the process of preparing hydrogel in Comparative Example 1, it was found that if only riboflavin photo-crosslinked silk protein was used, the concentration of riboflavin must be extremely high, and because the gelation rate of pure riboflavin photo-crosslinked silk protein was extremely slow, it required ultraviolet light irradiation for 1-3 hours to form a gel. The resulting gel was viscous and had poor formation.
[0070] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A highly elastic silk fibroin hydrogel, characterized in that: The highly elastic silk fibroin hydrogel is obtained by adding riboflavin and hydrogen peroxide to a silk fibroin solution and performing photocuring under ultraviolet light; The specific steps of its preparation method are as follows: S1. preparing a silk fibroin solution: placing raw silk in a sodium carbonate aqueous solution and heating and soaking it for degumming to obtain degummed silk fibroin fibers, immersing the obtained degummed silk fibroin fibers in a LiBr aqueous solution and heating and dissolving them to obtain a crude solution, placing the obtained crude solution in a dialysis bag, and dialyzing it in deionized water at low temperature, filtering the dialyzed solution to remove impurities and diluting it to obtain a silk fibroin solution, wherein the concentration of the silk fibroin solution is 1.5-7wt%; S2, uniformly mixing the silk fibroin solution obtained in step S1 with the riboflavin aqueous solution to obtain a mixed solution, wherein the concentration of the riboflavin aqueous solution is 0.05-10 mM, and the volume ratio of the silk fibroin solution to the riboflavin aqueous solution is 5-20:1, and then adding a hydrogen peroxide solution to the mixed solution, wherein the volume percentage concentration of the hydrogen peroxide solution is 5-30%, and the volume ratio of the hydrogen peroxide solution to the mixed solution is 1:5-30, and the pre-reaction solution is obtained after sufficient mixing; S3. The pre-reaction solution obtained in step S2 is placed under an ultraviolet lamp for photocuring to obtain a highly elastic silk fibroin hydrogel. The power of the ultraviolet lamp is 100-900 W, and the photocuring reaction time is 2-30 min.
2. A method for preparing the highly elastic silk fibroin hydrogel according to claim 1, characterized in that: The specific steps are as follows: S1. preparing a silk fibroin solution: placing raw silk in a sodium carbonate aqueous solution and heating and soaking it for degumming to obtain degummed silk fibroin fibers, immersing the obtained degummed silk fibroin fibers in a LiBr aqueous solution and heating and dissolving them to obtain a crude solution, placing the obtained crude solution in a dialysis bag, and dialyzing it in deionized water at low temperature, filtering the dialyzed solution to remove impurities, and diluting it to obtain a silk fibroin solution; S2, mixing the silk fibroin solution obtained in step S1 and the riboflavin aqueous solution uniformly to obtain a mixed solution, and then adding the hydrogen peroxide solution to the mixed solution, and mixing them thoroughly to obtain a pre-reaction solution; S3, placing the pre-reaction solution obtained in step S2 under ultraviolet light for photocuring to obtain a highly elastic silk fibroin hydrogel.
3. The method for preparing the highly elastic silk fibroin hydrogel according to claim 2, characterized in that: The concentration of the sodium carbonate aqueous solution in S1 is 0.1-0.5wt%, the mass volume ratio of the raw silk to the sodium carbonate aqueous solution is 1g / 10-100mL, the degumming treatment temperature is 45-100°C, and the degumming treatment time is 1-8h.
4. The method for preparing the highly elastic silk fibroin hydrogel according to claim 2, characterized in that: S1 The concentration of the LiBr aqueous solution is 1-10 mol / L, the mass volume ratio of the degummed silk fibroin fiber to the LiBr aqueous solution is 1 g / 1-20 mL, the degummed silk fibroin fiber is immersed in the LiBr aqueous solution and heated to dissolve at a temperature of 45-85° C., and the heating and dissolving time is 0.5-3 h.
5. The method for preparing the highly elastic silk fibroin hydrogel according to claim 2, characterized in that: The S1 low-temperature dialysis temperature is 0~4℃, and the low-temperature dialysis time is 1~5d.
6. Application of the highly elastic silk fibroin hydrogel according to claim 1 in the field of preparing biomedical materials and preparing 3D printing substrates.